PRAKTEK KEWARGAAN MASYARAKAT ADAT TOLOTANG DALAM MENGAKSES PELAYANAN DASAR PEMERINTAH DI KABUPATEN SIDRAP - Abidin, Nursam (LPPM Universitas Madako Tolitoli, 2025)
ABSTRACT This study explores the practice of indigenous peoples' citizenship in obtaining basic government services, namely in the fields of education and health. This research was conducted in the Tolotang indigenous community in Sidrap Regency, South Sulawesi Province. The Tolotang indigenous people are some of the indigenous peoples who still maintain their beliefs and culture, namely the belief in Dewata Suae. Indigenous peoples of Tolotang are people who are also indigenous peoples in the course of their history experiencing various interventions from the local government and the central government, one of which is the state which affiliated them to one religion from the six official religions recognized by the state. Three problem formulations are the focus of this research: first, tracking the civic practices of the Tolotang indigenous people in accessing basic services. Second, look at the extent to which the identity provided affects access to basic government services. Third, explore the various challenges they face in accessing basic government services. This study uses a descriptive approach and takes place during the period from April to June 2021, researchers make direct observations at the research location by participating and interacting directly with Indigenous peoples by involving themselves directly (live-in). This study found that the civic practice of the Tolotang indigenous people in accessing public services was heavily influenced by the New Order's policies which made them part of the Hindu religion, this certainly affected government processes such as education. This study finds that the national-religious curriculum in schools in Amparita has a direct impact on students because they have to study subjects that are not their religious beliefs. Keywords: Tolotang, Indigenous Peoples, Citizenship, Sect.